Budget repair or budget spectacle? The passage of Wisconsin's Act 10. Issue 7 (9th November 2016) - Pernsteiner, Aimee; Becker, D'Arcy; Fish, Matthew; Miller, William F.; Drum, Dawna
Abstract : Strategic planning processes use budgets to implement control and accountability. However, budgets can also be used to generate support for strategic decisions, for example by creating a political spectacle. A political spectacle is a problem engineered to have a specific political impact. This paper investigates politicians' use of a state budget as a political manoeuvre to defend strategic decisions regarding public employee unions in Wisconsin. The analysis shows how the 2011 state budget in Wisconsin was used to create a political spectacle to generate support for eliminating collective bargaining for public workers, especially public (state) school teachers.